Sedentary behavior and body composition in children of low-and mid-income countries: a review - Paulo Henrique Guerra; Evelyn Helena Corgosinho Ribeiro; Ana Carolina Barco Leme; Jorge Mota; José Cazuza Farias Júnior; Alex Antonio Florindo (Revista Brasileira de Atividade Física e Saúde)
This study reviewed the relationship between sedentary behavior (SB) and body composition in children and adolescents from low-and-mid income countries (LMIC). A systematic review was developed through manual and electronic searches in eight databases. Were included observational studies conducted in LMIC, with children and adolescents from three to 19 years. As results, 39 original articles were found (37 cross-sectional, 1 case control study and 1 cohort), which in all presented 75 analyzes, most of them based on screen behaviors (n = 71; 94.7%). At all, 15 of 25 analyses showed risk associations between SB and unfavorable body composition. When focusing on the dose of sedentary behavior, risk associations were verified in distinct cut of points: 1h/d (3 of 3 analyses); 2h/d (9 of 16); 3h/d (2 of 5); 4h/d (4 of 5) and 5h/d (3 of 6). Television time was the SB type most frequently associated as risk in all categories. In conclusion, recognition of these associations is important both to support future studies and for its dissemination in preventive messages in the population of interest. Also, further longitudinal studies are necessary for narrowing the casual relationships between the variables.